α-glucosidase Inhibitory Activity of Probiotic Isolate LBSU9 Isolated from Traditional Food “Trites”: a Preliminary Study - Fachrial, Edy; Ismawati, Ismawati; Nugroho, Titania T; Saryono, Saryono (Institute of Computer Science (IOCS), 2024)
As the prevalence of type 2 diabetes mellitus continues to increase over the years, research into antidiabetic drugs needs to continue. Probiotics are non-pathogenic microorganisms that have potential as α-glucosidase inhibitors. This study aimed to characterize and determine the α-glucosidase inhibitor activity of LBSU9 isolate, a probiotic isolated from